Ultrasonographic evaluation of post-COVID long-term lung changes and relation to prolonged COVID symptoms: a prospective cross-sectional study - Tan Tabakoğlu, Nilgün; Hancı Yılmaztürk, Pervin; Yılmam, İlker; Süt, Necdet; Hatipoğlu, Osman Nuri (The European Research Journal, 2024)
Objectives: This study aims to evaluate lung findings using lung ultrasonography (USG) in patients with PCR-positive COVID-19 pneumonia treated in the ward or intensive care unit and to explore the relationship with prolonged COVID-19 symptoms. Methods: This prospective cross-sectional study was conducted at the University Medical Faculty Hospital outpatient clinic from December 2022 to April 2023. It involved 54 adult patients with PCR-positive COVID-19 pneumonia, treated and discharged from the ward or intensive care unit (ICU). Clinical and demographic data, lung ultrasonography results, and prolonged COVID-19 symptoms were recorded. Results: Among the 54 patients, the ICU group had a mean age of 52.84 ± 12.30 years, while the ward group had a mean age of 58.80 ± 11.36 years (P=0.085). Shortness of breath was the most common prolonged symptom in both groups. The ICU group had significantly more right lung B lines than the ward group (P=0.002). Myalgia was more frequent in the ward group (P=0.024). No significant differences were observed in other variables (P>0.05). Prolonged COVID-19 symptoms were interrelated (P